Novel Portable Device for Post Mortem Interval Estimation Using Vitreous Humor Analysis - Louise Lijcklama à Nijeholt; Michael Fleermann; Micky Breukers; Jaap Knotter; Steven Staal; Brigitte Bruijns (Forensic Sciences, 2025)
Background: Accurately determining the post mortem interval (PMI) is critical in forensic investigations to reconstruct the sequence of events leading up to and following death. Traditional methods (e.g., observing livor mortis, rigor mortis, and using temperature-based models) have limitations due to their empirical nature and susceptibility to environmental variables. The objective of this study was to assess the potential of a novel portable device, the Fisic Medimate™ system, for estimating PMI through the analysis of the potassium/sodium (K+/Na+) ratio in vitreous humor. Method: Vitreous humor samples were collected from pigs at various intervals up to 44.5 hours post-mortem. These samples were analyzed using the Fisic Medimate™ system to determine the K+/Na+ ratio. The analysis was conducted at different time points to establish a relationship between the K+/Na+ ratio and PMI. Results: The results indicated a log-linear relationship between the K+/Na+ ratio and PMI for periods up to 31 hours, with normal residuals. This relationship was observed across all samples, suggesting that the method provides reliable and consistent data. Conclusions: This method offers a rapid and portable solution for PMI determination, providing valuable data within minutes directly at the crime scene. While these findings suggest potential for on-site forensic applications, further validation under real-world conditions is required to confirm its broader applicability.